Hydrogen from catalytic non-thermal plasma-assisted steam methane reforming reaction - Bajpai, Abhinav; Mehta, Shweta; Joshi, Kavita; Kumar, Sushant (International Journal of Hydrogen Energy, 2023)
Steam methane reforming reaction was carried out in a dielectric barrier plasma reactor. A systematic study is conducted to understand the influence of input power, flow rate, and water for the conversion, yield, and selectivity of the reaction over strategically designed catalysts. In particular, the production rate and selectivity of the products (H2, CO and C2 hydrocarbons) are monitored. CeO2 was used as packing material, mixed with oxides of manganese or copper and their combination. The optimum Cu/CeO2 catalyst illustrated the production rate of 248.7 mmolg-1h-1 and 11.25 mmolg-1h-1 for H2, and CO, respectively at specific energy input of 19.8 JL-1. DFT calculations exhibit apparent change in electronic structure of the CeO2 after inclusion of oxides of manganese and copper that enhance interaction with methane. Based on these findings, a plausible mechanism is elucidatedSteam methane reforming reaction was carried out in a dielectric barrier plasma reactor. A systematic study is conducted to understand the influence of input power, flow rate, and water for the conversion, yield, and selectivity of the reaction over strategically designed catalysts. In particular, the production rate and selectivity of the products (H2, CO and C2 hydrocarbons) are monitored. CeO2 was used as packing material, mixed with oxides of manganese or copper and their combination. The optimum Cu/CeO2 catalyst illustrated the production rate of 248.7 mmolg-1h-1 and 11.25 mmolg-1h-1 for H2, and CO, respectively at specific energy input of 19.8 JL-1. DFT calculations exhibit apparent change in electronic structure of the CeO2 after inclusion of oxides of manganese and copper that enhance interaction with methane. Based on these findings, a plausible mechanism is elucidated which can help to design catalyst for other applications in non-thermal plasma atmosphere. & COPY; 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: DFT; Dielectric barrier discharge; Non-thermal plasma; selectivity; Specific energy input; Steam methane reforming

Photoinduced CO2 and N2 reductions on plasmonically enabled gallium oxide - Ojha, Niwesh; Thakkar, Kavita; Bajpai, Abhinav; Joshi, Kavita; Kumar, Sushant (Journal of Colloid and Interface Science, 2023)
Ag-containing ZnO/ b-Ga2O3 semiconductor, which exhibit reduced bandgap, increased light absorption, and hydrophilicity, have been found to be useful for photocatalytic CO2 reduction and N2 fixation by water. The charge-separation is facilitated by the new interfaces and inherent vacancies. The Ag@GaZn demonstrated the highest photocurrent response, about 20-and 2.27-folds that of the Ga and GaZn sam-ples, respectively. CO, CH4, and H2 formed as products for photo-reduction of CO2. Ag@GaZn catalyst exhibited the highest AQY of 0.121 % at 400 nm (31.2 W/m2). Also, Ag@GaZn generated 740 lmolg-1 of NH4+ ions, which was about 18-folds higher than Ga sample. In situ DRIFTS for isotopic-labelled 13CO2 and 15N2 reaffirmed the photo-activity of as-synthesized catalysts. Density functional theory pro-vided insight into the relative affinity of different planes of heterostructures towards H2O, CO2 and N2 molecules. The structure-photoactivity rationale behind the intriguing Ag@GaZn sample offers a funda-mental insight into the role of plasmonic Ag and design principle of heterostructure with improved pho-toactivity and stability.(c) 2022 Elsevier Inc. All rights reserved.
Keywords: CO2 reduction; DRIFTS density functional theory; hydrophilicity; Photocurrent response